Impact of disability status on suicide risks in South Korea: Analysis of National Health Insurance cohort data from 2003 to 2013. Issue 1 (January 2017) - Lee, Sang-Uk; Roh, Sungwon; Kim, Young-eun; Park, Jong-Ik; Jeon, Boyoung; Oh, In-Hwan
Abstract: Background: The elevated risk of suicide in people with disability has been suggested in the previous studies; however, the majority of study results have been limited to specific disability types, and there is a lack of research comparing the risk of suicide in people with disability in general. Objectives: To examine the hazard ratio of suicide according to the presence and the types of disability and identify patterns in the results. Methods: In this study, we used National Health Insurance Service-National Sample Cohort data on 990, 598 people, and performed analysis on the cause of death from 2003 through 2013. A Cox proportional hazard model was used to estimate the hazard ratio of suicide associated with disability and its types. Results: The hazard ratio of suicide among people with disability was 1.9-folds higher compared to people without disability. The risk of suicide among different disability types was higher in mental disorder, renal failure, brain injury and physical disability. The hazard ratio of suicide in people with disability was not varied by income. The time to death by suicide for people with disability from the onset of their disability was 39.8 months on average. Conclusions: Our findings suggest that when the government plans suicide prevention policies, early and additional interventions specific to people with disability are needed. Disability due to mental disorder, renal failure should be given priority.